1971
DOI: 10.1172/jci106762
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the extent of myocardial infarction in the conscious dog by means of analysis of serial changes in serum creatine phosphokinase activity

Abstract: A B S T R A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
0
4

Year Published

1973
1973
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(132 citation statements)
references
References 24 publications
8
120
0
4
Order By: Relevance
“…At least in part it represents loss into the plasma since a correlation exists between loss of myocardial CPK activity and the appearance of CPK in the plasma.26 Also, it has been shown that CPK leaks from the injured area through the lymphatics.27 The observed correspondence between depression of tissue CPK activity and histologic necrosis is consistent with earlier studies.20 26,28 Our conclusions concerning the beneficial effects of an F102 of 0.40 are further strengthened by the observation that epicardial ST-segment elevation following coronary occlusion reflects reduction of cellular PO2,29…”
Section: Discussionsupporting
confidence: 65%
“…At least in part it represents loss into the plasma since a correlation exists between loss of myocardial CPK activity and the appearance of CPK in the plasma.26 Also, it has been shown that CPK leaks from the injured area through the lymphatics.27 The observed correspondence between depression of tissue CPK activity and histologic necrosis is consistent with earlier studies.20 26,28 Our conclusions concerning the beneficial effects of an F102 of 0.40 are further strengthened by the observation that epicardial ST-segment elevation following coronary occlusion reflects reduction of cellular PO2,29…”
Section: Discussionsupporting
confidence: 65%
“…In addition to these changes, an increase in sympathetic activity seems to be an important regulatory alteration. Increased activity of the sympathetic nervous system has been implicated in the morbidity induced by myocardial infarction (23,24), and this augmented sympathetic activity facilitates the development of cardiac arrhythmias and the increased extension of the ischemic injury (25) and contributes to some extracardiac regulatory alterations such as sodium balance, with sodium retention expanding extracellular fluid volume (14). This compensatory mechanism may be seen as a compensatory phenomenon acting to preserve the hemodynamic balance despite the decreased cardiac output induced by ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial CK depletion measured directly from the myocardium, as an index of infarct size, is independent of CK released into the plasma and has been shown to correlate closely with morphology in a variety of animals including the rat (Maclean et al, 1976), dog (Shell et al, 1971), baboon (Yasmineh et al, 1977), and the rabbit (Kjekshus and Sobel, 1970). This correlation is unaffected by a variety of interventions including propranolol (Maroko et al,197 1 ), hyaluronidase (Maroko et al, 1972), nifedipine (Henry et al, 1978), nitroglycerin (Epstein et al.…”
Section: Discussionmentioning
confidence: 99%